Analysis The Impact of Liquidity Ratios, Activity Ratios, and Leverage Ratios on Profitability With Firm Size as A Moderating Variable (an Empirical Study of Transportation Sector Companies Listed on The Jakarta Stock Exchange From 2018 To 2022) - Muhammad Akbar; Rahmat Nugraha (International Journal Labs, 2025)
This study aims to explore not only the direct effects of Liquidity Ratio (Return on Assets), Activity Ratio (Total Asset Turnover), and Leverage Ratio (Debt to Asset Ratio) on profitability but also how firm size moderates these relationships. The data collection method employed in this research is documentation, utilizing data from existing records. Data analysis was conducted using Moderated Regression Analysis (MRA) and processed with SPSS version 25. The findings reveal that the Current Ratio (CR) and Debt to Asset Ratio (DAR) have a positive and significant impact on corporate profitability (ROA). Conversely, Total Asset Turnover (TATO) does not significantly influence ROA, indicating that corporate assets have not been utilized optimally. Furthermore, Firm Size acts as a moderator that strengthens the relationship between liquidity, leverage, and activity ratios on profitability. Larger firms tend to exhibit greater operational efficiency and better resource access, making them more effective in enhancing profitability compared to smaller firms. Firm size is also shown to have a direct impact on ROA.